(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Nephrotic syndrome (NS) is one of the most common childhood kidney diseases where defective immune system increases the chances of various infections. Forecasting the prognosis and proper planned management based on the recent data of risk factors and infection patterns can reduce the associated morbidities and mortalities. We investigated the incidences of infection and associated risk factors among the hospitalized children to provide an updated view of the current infection pattern of children with NS. This observational study was conducted at the Department of Pediatrics, Bangabandhu Sheikh Mujib Medical College Hospital, Bangladesh, from July 2017 to June 2020. A total of 167 children aged <_12 years admitted at BSMMCH during this period with NS were included in this study. The hospital course and associated investigation reports of the study participants were analyzed. The incidence of infection among the patients with NS was 21.56%. The mean age of the participants was 5.43 2.66 years, and 73.01% of them were under immunosuppressive therapy. Ascites was a significant presentation among the infection group. There were no significant differences in Hb%, serum albumin, serum cholesterol and 24h urinary protein level between the two groups. Klebsiella and Escherichia coli were predominant isolates in the blood and urine culture, respectively. Serum albumin level <1.5 g/dL was associated with infection in risk analysis. Peritonitis, UTI and pneumonia were common infections and patients with associated infections had a significantly longer hospital stay (p = <0.001). Identifying the risk groups with ascites and low serum albumin levels and hospital-based predominant infectious organism patterns can help develop planned management of patients with NS associated various infections. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):29-32